Penerapan Implemetasi Desain dan Evaluasi Sumatif di Sekolah Dasar SDN Pakulanan 2 Tangerang Selatan - Faujiah, Alya Nur; Habsah, Dinda (Lembaga Yasin AlSys, 2022)
Evaluation of learning includes measurement and assessment of the learning outcomes of learners. Thus, the evaluation should be carried out with the best in order to avoid errors in measuring and assessing the learning outcomes of learners. A good evaluation is an evaluation that is done by basing themselves on the principles that have been established. Among these principles is the principle of continuity. The principle of continuity requires the evaluator to continuously evaluate from time to time in order to get a correct conclusion on the learning outcomes of the learners.